Nickel-catalyzed decarbonylation of N-acylated N-heteroarenes - Morioka, Toshifumi (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Nickel-catalyzed decarbonylation of N-acylated N-heteroarenes is developed. This method can be used to produce a variety of N-aryl heteroarenes, including pyrroles, indoles, carbazoles and phenoxazines, using benzoic acid derivatives as arylating reagents. Arylnickelamide intermediates that are relevant to the catalytic reaction were characterized by X-ray crystallography. When N-acylated benzimidazoles are used as substrates, decarbonylation accompanied 1,2-migration to form 2-arylated benzimidazoles.